PENGARUH KESADARAN WAJIB PAJAK DAN PEMAHAMAN WAJIB PAJAK TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI DENGAN SANKSI PAJAK SEBAGAI MODERASI - Lorista, Firshona; Subroto, Melvin Rahma Sayuga (Politeknik Negeri Ambon, 2025)
Introduction: Taxpayer compliance in Indonesia remains a significant concern, despite advancements in awareness and understanding of tax obligations. This study aims to examine the influence of taxpayer awareness and comprehension on individual taxpayer compliance, with tax consequences serving as a moderating variable.Method: A quantitative methodology was employed, utilizing a sample of 86 respondents selected via simple random sampling. Data were gathered via a structured questionnaire employing a five-point Likert scale and analyzed with SmartPLS 4.0 for Partial Least Squares Structural Equation Modeling (PLS-SEM).Result: The findings demonstrate that taxpayer knowledge and comprehension significantly enhance compliance. The R-square value of 0.874 for the compliance variable indicates substantial explanatory power of the model. The moderating effect of tax penalty was determined to be statistically insignificant. This research contributes to the literature by addressing the gap in studies on digital investor taxpayers in Indonesia and highlights the limited significance of sanctions as moderating factors. The results underscore the need to improve taxpayer education and awareness initiatives to foster sustained compliance behavior. Keywords: Compliance level, Taxpayer awareness, Taxpayer understanding, Tax sanctions, Theory of Planned Behavior, SmartPLS.